Ett bidrag till teorin om det svenska perfektums utveckling - Sadalska, Genowefa (Wydawnictwo Naukowe UAM, 1992)
An attempt is made to account for the development of the Swedish perfect tense. The analysis is based on Kuiylowicz’s theory on the origin of temporal categories. The Swedish perfect tense is derived from periphrastic present constructions which denote present states resulting from past events. The constructions tend to develop the temporal meaning of Past (Praeteritality while gradually reducing that of Present (Presentavity). This development is caused by the processes of delexicalization and grammaticalization. The Swedish perfect tense, however, has not yet reached the stage of pure Praeteritality though in certain contexts it can already be determined by temporal adverbs primarily referring to the Past.
A Contribution to the theory on the development of the Swedish perfect tense